2019
DOI: 10.1097/ta.0000000000002414
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with postinjury hypercoagulability

Abstract: Background: Obesity is linked to hypercoagulability with an increased risk of venous thromboembolic events (VTE) in the uninjured population. Therefore, we hypothesize that obesity (Body Mass Index (BMI) ≥30 kg/m2) is associated with a hypercoagulable state postinjury characterized by increased clot strength and resistance to fibrinolysis. Methods: Our prospective Trauma Activation Protocol database includes all trauma activations patients for whom a rapid thrombelastography (TEG) is obtained within 60 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…In our adjusted analyses increased BMI, increased time from injury to TXA administration, and increased amount of blood transfusions were all independently associated with increased risk of thromboembolism. This is consistent with the literature that indicates hypercoagulability and increased risk of thrombotic events in patients with obesity 19–22 . The independent association with thromboembolism and later use of TXA within a 2‐h time frame from injury may be due to increased endothelial injury, inflammation, and hypercoagulability that increases from the time of admission to 6 h after admission in severely injured patients, as is demonstrated by increasing concentrations of syndecan‐1, IL‐8, PF1.2, and D‐dimer during this time frame in the study (Figure 2).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our adjusted analyses increased BMI, increased time from injury to TXA administration, and increased amount of blood transfusions were all independently associated with increased risk of thromboembolism. This is consistent with the literature that indicates hypercoagulability and increased risk of thrombotic events in patients with obesity 19–22 . The independent association with thromboembolism and later use of TXA within a 2‐h time frame from injury may be due to increased endothelial injury, inflammation, and hypercoagulability that increases from the time of admission to 6 h after admission in severely injured patients, as is demonstrated by increasing concentrations of syndecan‐1, IL‐8, PF1.2, and D‐dimer during this time frame in the study (Figure 2).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the literature that indicates hypercoagulability and increased risk of thrombotic events in patients with obesity. [19][20][21][22] The independent association with thromboembolism and later use of TXA within a 2-h time frame from injury may be due to increased endothelial injury, inflammation, and hypercoagulability that increases from the time of admission to 6 h after admission in severely injured patients, as is demonstrated by increasing concentrations of syndecan-1, IL-8, PF1.2, and D-dimer during this time frame in the study (Figure 2). The mechanisms for the role of TXA increasing the risk of thrombotic events for patients with laboratory measures of increased endothelial injury, inflammation, and clot formation require additional investigation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, VTE risk was lower among patients older than 50 years than among younger patients [ 16 ]. In a prospective study of 687 trauma patients to examine the relationship between obesity [body mass index (BMI) ≥ 30 kg/m 2 ] and post-injury hypercoagulability, obese patients showed higher MA values, lower fibrinolysis [clot lysis achieved 30 min after MA (LY30%)], and higher incidence of VTE than non-obese patients [ 17 ]. A study of 72 morbidly obese patients undergoing bariatric surgery showed that the average BMI of obese patients decreased from 44.6 kg/m 2 to 31.4 kg/m 2 by 6 months after surgery.…”
Section: Introductionmentioning
confidence: 99%